2019
DOI: 10.1111/jhn.12701
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index and mortality: a cohort longitudinal study in a Mediterranean area

Abstract: BackgroundHigher Dietary Inflammatory Index (DII®) scores are associated with increased morbidity and mortality. However, little is known about the effects of DII on mortality in Mediterranean countries. Therefore, in the present study, we aimed to investigate the potential association between DII scores and overall, cancer and cardiovascular disease (CVD) mortality in people living in a Mediterranean area.MethodsDII scores were calculated using a validated food‐frequency questionnaire. DII scores were then ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
1
9
2
Order By: Relevance
“…Considering that NAFLD has been associated with a systemic and hepatic proinflammatory state and that inflammatory cytokines and chemokines, including tumor necrosis factor‐α, interleukin‐6 and high‐sensitivity C‐reactive protein (hs‐CRP), are increased in patients with NAFLD and NASH, 14 it should be hypothesised that an anti‐inflammatory diet could lead to an improvement in liver status. Previous studies have shown that the inflammatory potential of the diet is associated with mortality, metabolic syndrome and hepatic markers and therefore might be an important predictor of NAFLD 15–20 . Furthermore, it has been shown that the Mediterranean diet, a diet characterised by an anti‐inflammatory dietary pattern, might have a beneficial role in the onset and severity of NAFLD 21–23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that NAFLD has been associated with a systemic and hepatic proinflammatory state and that inflammatory cytokines and chemokines, including tumor necrosis factor‐α, interleukin‐6 and high‐sensitivity C‐reactive protein (hs‐CRP), are increased in patients with NAFLD and NASH, 14 it should be hypothesised that an anti‐inflammatory diet could lead to an improvement in liver status. Previous studies have shown that the inflammatory potential of the diet is associated with mortality, metabolic syndrome and hepatic markers and therefore might be an important predictor of NAFLD 15–20 . Furthermore, it has been shown that the Mediterranean diet, a diet characterised by an anti‐inflammatory dietary pattern, might have a beneficial role in the onset and severity of NAFLD 21–23 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the inflammatory potential of the diet is associated with mortality, metabolic syndrome and hepatic markers and therefore might be an important predictor of NAFLD. [15][16][17][18][19][20] Furthermore, it has been shown that the Mediterranean diet, a diet characterised by an anti-inflammatory dietary pattern, might have a beneficial role in the onset and severity of NAFLD. [21][22][23] However, the relationship between the Dietary Inflammatory Index (DII), a literature-derived dietary index that was developed to predict inflammation, 24 and the LSM and CAP assessed by transient elastography has not been investigated previously.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, diet rapidly and reversibly changes gut microbiota composition (73). Higher dietary inflammatory index associates with increased risk of cancer (74). In a primate model, Mediterranean diet leads to enrichment of Lactobacillus, Clostridium, Faecalibacterium, and Oscillospira genus, and decline of Ruminococcus and Coprococcus population (75), a pattern that has also been observed in humans following a vegetarian diet versus omnivore diet (76).…”
Section: Microbiota Modulations As Adjuvant Cancer Therapymentioning
confidence: 94%
“…The DII ® has been validated with various inflammatory markers. A more pro-inflammatory dietary pattern has been associated with higher mortality risk [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%